2008
DOI: 10.1007/s11237-008-9047-4
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of the energetic nonhomogeneity of the surface of oxide and carbon materials

Abstract: The molecular statistical method for evaluating the distribution of active sites of various adsorbents relative to their energies has been improved. This method is used not only for the treatment of experimental data on the adsorption of hydrocarbons on various adsorbents, which is the usual procedure, but also data on the adsorption of polar water and methanol molecules on the active sites of adsorbent surfaces. Two types of active sites differing in energy have been shown to exist on the surface of graphitiz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2010
2010
2012
2012

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…(8)-(10) become identical to Eqs. (5)-(7) in [12]. If, in addition, each centre can accommodate not more than one molecule, then (as shown above) all vanish, and Eq.…”
Section: Methodsmentioning
confidence: 85%
See 1 more Smart Citation
“…(8)-(10) become identical to Eqs. (5)-(7) in [12]. If, in addition, each centre can accommodate not more than one molecule, then (as shown above) all vanish, and Eq.…”
Section: Methodsmentioning
confidence: 85%
“…Phenolic hydroxyl groups are less acidic, and possess much lower sorption activity [4,10]; however the density of these groups on the surface of graphitised thermal black and thermally expanded graphite is higher than that of the carboxyl groups [11]. Ab initio calculations [12] have shown that the adsorption of one water or methanol molecule on the carboxyl centre results in the formation of two hydrogen bonds: between the oxygen atom of the hydroxyl group and the proton of adsorbed molecule, and between the proton of the hydroxyl group and the oxygen atom of adsorbed mol ecule. On the contrary, the adsorption on the weakly acidic phenolic hydroxyl group results in the forma tion of one hydrogen bond only.…”
Section: Introductionmentioning
confidence: 99%
“…Carbon adsorbents are characterized by carboxyl, phenolic, hydroxyl, and other active sites. The reasons for energetic heterogeneity have been analyzed in detail by various workers [1][2][3][4][5].Various physical methods are used to study the energetic heterogeneity. Atomic force microscopy [6] and high resolution electron microscopy [7] are among the most common methods for oxides and silicates.…”
mentioning
confidence: 99%
“…Carbon adsorbents are characterized by carboxyl, phenolic, hydroxyl, and other active sites. The reasons for energetic heterogeneity have been analyzed in detail by various workers [1][2][3][4][5].…”
mentioning
confidence: 99%